Research on a Web Services Discovery Method Based on Virtual Social Network - Shanliang Pan; Qinjiao Mao; Lu Han (Dianxin kexue)
A Web services discovery method based on virtual social network was proposed, looking for services to meet user requirements from the mutual competition and collaboration service relationship. In the competition, the method selected a group of competitive service list by calculating the text similarity and structural similarity between services, and then according to the cooperation relations, calculated the intercourse skills of the list of all services, recommended the strong communication ability of service to the user, realized the combination of user service process. Comparing the recall rate and accuracy with other methods, the validity of this method is verified.